Examining How Supplemental Instruction Impacts Students’ Motivation in Organic Chemistry - Guyot, Michael; Hsu, Samantha; Nizomov, Javlon; Antonenko, Pavlo; Habenicht, Stefanie (IJCER (International Journal of Chemistry Education Research), 2024)
This study investigates the effect of Supplemental Instruction (SI) on students’ motivation and learning outcomes in an introductory Organic Chemistry course for non-majors. SI, conducted by experienced facilitators, offers a range of academic support for students that may include reviewing challenging concepts, working through practice problems, and answering student questions. To assess the impact of SI in this Organic Chemistry course, we measured several parameters: student engagement during SI sessions, exam scores and final course grades, as well as self-reported motivation levels at both the beginning and end of the semester. We performed a linear regression analysis and observed a positive correlation between SI participation and improved performance on certain exams for SI participants. Further analysis showed that student motivation alone could be driving these improvements. These results suggest that while SI may be beneficial for some students, greater emphasis should be placed on ensuring that students are motivated to learn difficult concepts.